Managerial Corporate Criminal Liability and Restorative Justice in Indonesian Corruption Cases: A Doctrinal and Policy Analysis - Abels Selasih; Herry Febriadi (Global Insights in Management and Economic Research, 2025)
Purpose of the study: Corruption remains a critical issue in Indonesia, hindering clean and just governance. Traditional retributive justice focuses on punishment without addressing loss recovery or societal restoration. Restorative justice offers an alternative approach emphasizing relationship restoration and stakeholder balance. Materials and methods: This study employs normative legal research (doctrinal research) focusing on legal principles, norms, and regulations. Using statutory, conceptual, and case approaches, data were collected through library research analyzing primary legal materials (legislation and court decisions), secondary materials (books and journals), and tertiary materials (legal dictionaries). Data analysis utilized qualitative juridical techniques for systematic legal interpretation. Results: Despite supportive regulations for corporate criminal liability, implementation challenges persist. Restorative justice demonstrates effectiveness in recovering losses and repairing relationships between perpetrators, victims, and society. The 2023 National Criminal Code formally recognizes corporations as criminal subjects, enhancing the relevance of restorative justice principles. Conclusions: Regulatory reform and enhanced education are necessary to improve understanding of corporate criminal liability and restorative justice. The integration of restorative justice principles in corruption cases can create more holistic justice outcomes while maintaining accountability.